Review paper Place of methotrexate in the treatment of psoriasis in the era of biologic agents - Dańczak-Pazdrowska, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Methotrexate (MTX) belongs to a group of drugs known as antimetabolites and is a structural analog of folic acid. It was used for the first time for the treatment of psoriasis over 50 years ago. Nowadays it is used in every type of moderate-to-severe psoriasis, including psoriatic arthritis, and is considered as the most effective disease modifying drug (DMARD). In this paper we review the current state of knowledge as regards mechanisms of action, effectiveness and toxicity of MTX in psoriatic patients as well as we present ways of its administration.